Pengaruh Skala Perusahaan, Pengungkapan Media Sosial, dan Akuntansi Lingkungan terhadap Praktik Greenwashing Perusahaan Sektor Industri yang Terdaftar di Bursa Efek Indonesia Periode 2023-2024 - Michael Lee; Siti Khairani (Universitas Muhammadiyah Palembang, 2026)
This study aims to analyze the effect of firm size, social media disclosure, and environmental accounting on greenwashing practices in industrial sector companies listed on the Indonesia Stock Exchange (IDX). The study is based on Legitimacy Theory, supported by Stakeholder Theory and Signaling Theory. A quantitative approach was applied using purposive sampling, involving 33 companies during the 2023–2024 period. Data were analyzed using multiple linear regression with SPSS. The results show that firm size has a negative but insignificant effect on greenwashing, social media disclosure has a negative and significant effect, while environmental accounting has a positive but insignificant effect. The coefficient of determination (R²) of 0.132 indicates that the model explains 13.2% of the variation in greenwashing. This study enriches the application of Legitimacy Theory in the context of greenwashing in emerging markets and implies that transparency on social media can serve as an effective monitoring tool for evaluating environmental performance for companies, regulators, and investors.